Revitalizing Special Libraries: Innovative Marketing Frameworks to Drive User Visits - Nurlela; Utep Ahmad Zulfiqor; Hardi Humaedi Hidayat (Journal of Educational Management Research, 2026)
This study aims to examine marketing strategies implemented by a library to increase user visits in the context of rapid information technology development and to identify factors influencing fluctuations in visitor numbers. It employs a qualitative descriptive approach with data collection through observation, interviews, and documentation. Results show that the library applies marketing strategies including relevant collection development, service quality improvement, social media promotion, and collaboration with educational institutions and communities. Visitor trends fluctuate due to internal and external factors, including digital information behavior changes, academic calendar cycles, service quality, facilities, comfort, and promotion effectiveness. The study implies that strengthening digital promotion, improving user centered services, and enhancing facilities can increase user engagement and visit interest. It highlights the need for integrated marketing strategies combining digital communication, service innovation, and community engagement to support sustainable library usage in the evolving digital information environment. These findings provide practical guidance for library managers in optimizing digital outreach strategies and improving service quality to attract and retain diverse user groups effectively over time.